Health literacy and adherence to the pharmacological treatment by people with arterial hypertension - Iorana Candido da Silva; Maria Rayssa do Nascimento Nogueira; Tahissa Frota Cavalcante; Gilvan Ferreira Felipe; Huana Carolina Cândido Morais; Rafaella Pessoa Moreira; Andressa Suelly Saturnino de Oliveira (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To analyze the association between health literacy and the adherence to the pharmacological treatment of Brazilians with arterial hypertension. Methods: Cross-sectional study with 234 participants who responded an on-line sociodemographic and clinical characterization questionnaire, in addition to evaluation of health literacy and of the adherence to their pharmacological treatment. Data were analyzed using descriptive statistics and difference and correlation tests. Results: People with post-graduation, who were actively working and did not smoke, had better health literacy results. Elders and those who were retired or lived on government subsidies adhered better to the medication treatment. There was a correlation between the numerical dimension (rs=0.189; p=0.004) and the global health literacy result (r2=0.170; p=0.009) with the adherence. Conclusions: A better numerical and global understanding of health literacy was associated with better adherence to arterial hypertension medication treatment.